Implementasi Pendidikan Multikultural sebagai Strategi Membentuk Karakter Peserta Didik - Kholik, Abdul; Ilham, Abdullah; Abdullah, Camelia Sabrina; Maimun, Maimun (Journal of Linguistics and Social Studies, 2025)
The formation of student character is a crucial issue that requires a comprehensive solution. One promising approach is through multicultural education. Multicultural education is very important to shape the character of students regarding the importance of harmony and mutual respect in diversity. This education emphasizes a comprehensive understanding of various cultures, so that it can create attitudes of tolerance, empathy and appreciation for differences. This education is not only limited to the transfer of knowledge, but also the formation of thought patterns, attitudes and actions that are based on national values. By instilling a strong national awareness, multicultural education aims to form individual characters who not only have academic competence, but also have integrity, tolerance and a high sense of love for the country. Through a literature review, this research will explain further the role of multicultural education strategies in building student character.